An Emergency Switch to Distance Learning in Response to the COVID-19 Pandemic: Experience from an Internationally Accredited Undergraduate Pharmacy Program at Qatar University - Farhat Naz Hussain (11105280) (2022)
The world is experiencing an unprecedented public health emergency owing to the COVID-19 pandemic. To control virus spread, many countries temporarily suspended classes. In this context, the availability of e-tools and distance learning platforms in higher education institutions has proven very useful to facilitate the emergency switch to distance learning to ensure continuity of the educational process. We discuss here the experience of the College of Pharmacy at Qatar University in responding to suspension of classes using available educational technologies. Furthermore, we provide some reflection points for optimal implementation of technology-enhanced learning into distance education for future academic years. Other Information Published in: Medical Science Educator License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s40670-020-01079-9